Relationship between nutritional status, respiratory performance and age : study among Tangkhul Naga females of Northeast India - Mungreiphy, N. K.; Kapoor, Satwanti; Sinha, Rashmi (Acta Biologica Szegediensis, 2012)
The study aims to examine relationship between nutritional status, respiratory performance and age. Cross-sectional study was carried out among 346 Tangkhul Naga females of Northeast India, ranging in age from 20-70 years. Height, weight, body mass index (BMI), breath holding time, chest expansivity and dynamic lung function tests like forced expiratory volume in one second, force vital capacity, forced expiratory ratio and peak expiratory flow rate were studied. The results showed that both low and high BMI were associated with poor lung functions, and showed inverse relationship. Subjects with normal BMI had better respiratory efficiency as compared to underweight, overweight/obese subjects. Age plays an important role in structural and functional change. BMI and lung functions were also associated with age. BMI increased with advancing age till middle age. Values of FEV 1.0, FVC, FER, PEFR, BHT and CE declined with advancing age indicating negative association of respiratory performance with age. BMI was also independently associated with lung functions and age. Age and BMI were positively correlated, but both age and BMI has negative associations with respiratory performances. Nutritional disorder had negative impact on lung functions. Evaluating the effect of age and BMI on lung functions showed that ageing had greater impact on respiratory performance.